Influence of Fossil Fuel Prices on Fossil and Renewable Electricity Consumptions, GDP, Inflation and Greenflation: A Case Study in the Asia Pacific Countries - Adi, Tri Wahyu; Susanto, Edy; Caswito, Ade; Yuwono, R. Sapto; Warsokusumo, Tarwaji; Nugroho, A. Y. Agung (International Journal of Energy Economics and Policy, 2024)
This study aims to examine the Influence of Fossil Fuel Prices on Fossil and Renewable Electricity Consumption, GDP, Inflation and Greenflation. This research is explanatory. The empirical analysis uses time-series data of Fossil Fuel Price, Fossil Electricity Consumption, Renewable Electricity Consumption, Inflation Rate and GDP in Asia Pacific Countries in the period 2016 – 2021. The inferential statistical method used to analyse this study is component-based using SmartPLS 4.0.9.6. The results of this study, find that fossil fuel price has a negative significant effect on fossil electricity consumption and a significant negative effect on renewable electricity consumption. Fossil electricity consumption has a significant negative effect on GDP and a negative insignificant effect on Inflation. Renewable electricity consumption has a positive significant effect on GDP and an insignificant negative effect on inflation (Greenflation). The novelty of this study is to examine how Fossil fuel prices have an effect on renewable electricity consumption and its impact on GDP and greenflation analysis using SmartPLS 4.0.9.6.